Biochemical and biophysical characterization of Leishmania donovani citrate synthase - Ranjan P.; Sarma M.; Dubey V.K. (My University, 2025)
Citrate synthase is a crucial enzyme in the TCA cycle and represents a potential therapeutic target. However, knowledge about this enzyme in Leishmania parasites remains limited. In this study, we have successfully cloned, expressed, and purified citrate synthase from Leishmania donovani (LdCS) using a bacterial system, and characterized it through various biophysical and biochemical methods. Circular dichroism analysis at physiological pH indicates that LdCS is properly folded. Further investigation into its tertiary structure using a quencher reveals that most tryptophan residues are located within the protein's hydrophobic core. Biochemical assays show that the recombinant enzyme is catalytically active, with optimal activity at pH 7.0. Kinetic studies provided parameters such as Km and Vmax. Enzyme inhibition assays revealed that LdCS activity is competitively inhibited by FDA-approved compounds—Abemaciclib, Bazedoxifene, Vorapaxar, and Imatinib—with Ki values ranging from 2 to 3 μM, demonstrating significant binding affinity. This research paves the way for exploring LdCS as a potential drug target for treating leishmaniasis. © 2024 Elsevier B.V.